Listening Learning Conditions in Indonesian Language in Grade 3rd Elementary School - Iqbal, Rahmat; Rahman (International Conference on Elementary Education, 2022)
This article aims to describe the conditions of listening learning in Indonesian language learning in class III SD Negeri Lamtheun. This research uses descriptive qualitative method with data analysis method according to Miles and Hubberman which has three steps, namely data reduction, data presentation and conclusion drawing. Data collection techniques using observation, interviews and questionnaires. By paying attention to the findings and analysis of the data obtained, this research has revealed the conditions of listening learning in Indonesian language learning in elementary schools that are currently less creative. The conditions for the inaccuracy of the listening learning process include; a) listening learning conditions are only carried out for the question and answer method, b) listening learning is carried out like reading learning, and c) the teacher's ability to tell the contents of the listening that is not good. This condition is also exacerbated because the use of media in listening learning is still lacking and the availability of media is also still difficult to find. The theoretical analysis in this article provides information that teachers should pay more attention to listening learning because listening skills are related to other learning processes. teachers should design effective listening learning and use appropriate media in order to achieve listening learning objectives.